Effect of Cr Concentration on the Optical and Magnetic Properties of Cr‐TiN Thin Films Grown by Reactive Magnetron Sputtering. Issue 5 (29th January 2023) - Abualgassem, Ebrahim; Maarouf, Monzer; Bake, Abdulhakim; Cortie, David; Alam, Khan; Haider, Muhammad Baseer
Abstract : Chromium‐doped titanium nitride thin films are deposited using RF/DC reactive magnetron co‐sputtering technique. Optical, chemical, surface morphology and magnetic properties of the deposited films are studied using spectrophotometry, X‐ray photoelectron spectroscopy, atomic force microscopy, and vibrating sample magnetometry, respectively. Films are prepared with different concentration of chromium by adjusting the sputtering power of magnetron using chromium target. A redshift in the bandgap of Cr‐TiN films is observed as a function of chromium concentration. X‐ray photoelectron spectroscopy confirms the presence of chromium in the films in third (Cr +3 ) and sixth (Cr +6 ) oxidation state. The films with lower concentration of chromium exhibit ferromagnetism with clear hysteresis loop at 3 K and at room temperature with higher saturation magnetization compared to the films grown with higher Cr concentration. Abstract : Chromium‐doped titanium nitride thin films are prepared at different chromium/titanium ratio using reactive magnetron co‐sputtering technique. The films with lower concentration of chromium exhibit ferromagnetism with higher saturation magnetization and coercivity compared to the films grown at higher chromium concentration. Ferromagnetism in low‐doped chromium concentration is attributed to long‐range ferromagnetic ordering of chromium atoms acting as bound magnetic polarons.